EPICE cohort: two-year neurodevelopmental outcomes after very preterm birth. Issue 4 (5th November 2019) - Draper, Elizabeth S; Zeitlin, Jennifer; Manktelow, Bradley N; Piedvache, Aurelie; Cuttini, Marina; Edstedt Bonamy, Anna-Karin; Maier, Rolf; Koopman-Esseboom, Corine; Gadzinowski, Janusz; Boerch, Klaus; van Reempts, Patrick; Varendi, Heili; et al.
Abstract : Objective: To determine whether the variation in neurodevelopmental disability rates between populations persists after adjustment for demographic, maternal and infant characteristics for an international very preterm (VPT) birth cohort using a standardised approach to neurodevelopmental assessment at 2 years of age. Design: Prospective standardised cohort study. Setting: 15 regions in 10 European countries. Patients: VPT births: 22 +0 –31 +6 weeks of gestation. Data collection: Standardised data collection tools relating to pregnancy, birth and neonatal care and developmental outcomes at 2 years corrected age using a validated parent completed questionnaire. Main outcome measures: Crude and standardised prevalence ratios calculated to compare rates of moderate to severe neurodevelopmental impairment between regions grouped by country using fixed effects models. Results: Parent reported rates of moderate or severe neurodevelopmental impairment for the cohort were: 17.3% (ranging 10.2%–26.1% between regions grouped by country) with crude standardised prevalence ratios ranging from 0.60 to 1.53. Adjustment for population, maternal and infant factors resulted in a small reduction in the overall variation (ranging from 0.65 to 1.30). Conclusion: There is wide variation in the rates of moderate to severe neurodevelopmental impairment for VPT cohorts across Europe, much of which persists following adjustment for known population, maternal and infant factors. Further work is needed to investigate whether other factors including quality of care and evidence-based practice have an effect on neurodevelopmental outcomes for these children.